TEACHING COMPETENCIES OF ART EDUCATION TEACHERS IN PRIMARY SCHOOLS (Journal of the College of Basic Education, 2022)
The current research aims to measure the level of teaching competencies for teachers of art education and then to identify the statistical differences of the gender variable between male and female teachers in teaching competencies , and the researcher adopted the descriptive research method .The current research sample consisted of (80) male and female teachers of art education in primary schools in the general directorate of education in diyalaThe researcher has prepared a tool a for the current research , which is .- skill test tool (observation form) observation and evaluation of the performance of art education teachers , in teaching competencies (cognitive – performance – interactive – productivity) and the observation form consisted of (65) paragraphs.The researcher used the following statistical methods to process the data(arithmetic mean ,standard deviation , t –test for two independent samples ,variance , hypothetical mean.Among the most important results of the current research .The results of the first goal:-The t-value amounted to( 273,19) which is a function in favor of the hypothetical mean , which means that the teachers of art education do not have teaching competencies.The results of the second goal :-The t-value amounted to (1,349) to be not statistically significant , which means that males and females have no statistically significant differences between male and female teachers in teaching competencies. Conclusions:-1- the study worked to improve and ralse the level of performance of art education teachers in the perf0rmance teaching competencies represented in planning implementation and evaluation .2-the possibility of training according to the standards of total quality , as it is an essential foundation in the field of education to achieve the satisfaction of the student and the guardian.Recommendation :-1-the need to take advantage of this study in training art education teachers on teaching competencies during the service.2- do another study that studies other variables such the variable of service , age and previous experience of teachers.Suggestions :-1- conducting a study similar to the current study with other dependent variables that were not addressed by the current study .2- the researcher suggests conducting a study that studies each adequacy separately.